Association between polymorphism in TaqI, BsmI, Apa1, DHCR7, GC, CYP27B1 and CYP24A1 genes and vitamin D deficiency in Saudi obese females - Bin obead, Manal; AlSedairy, Sahar Abdulaziz; Syed, Naveed Ahmed; Subbarayan, Periasamy Vaiyapuri; Aljurbua, Tahani; Aljuwayd, Maha Abdulaziz; Arzoo, Shaista; Alshatwi, Ali Abdullah (Progress in Nutrition, 2020)
Background. Obesity is an endemic disease and obese people requires larger vitamin D intakes toachieve normal 25(OH)2D3 as compared to individuals with normal weight. This study assessed the associationof vitamin D levels with the single nucleotide polymorphism (SNPs) of genes related to obesity and vitamin D(i.e., TaqI, BsmI, Apa1, DHCR7, GC, CYP27B1 and CYP24A1). Methods. One hundred forty two womenwere involved in this study. The study tools included interview questionnaire, anthropometric measurements(height, weight, BMI) and blood biochemical tests (glucose, insulin, cholesterol, triglyceride, HDL, LDL,25-Hydroxyvitamin D and parathyroid assessment and SNP analysis (VDR SNPs, DHCR7, GC, CYP27B1,CYP24A1). Results. As compared to normal vitamin D obese (NVD) subjects the weight, body mass index(BMI) and parathyroid hormone (PTH) was significantly higher in vitamin D deficient obese (VDD) subjects.While, total cholesterol (TC), triglyceride (TG) and vitamin D levels were significantly lower in the vitamin Ddeficient group compared to the normal vitamin D group. Various variants such as TaqI, BsmI, Apa1, DHCR7,GC rs4588 and CYP27B1 did not showed any significant association with the pathogenesis of vitamin Ddeficiency related obesity. However, GC rs7041 and CYP24A1 genotypes were significantly related with vitaminD deficiency in patients with obesity. Conclusion. This study suggests that polymorphisms in the GC andCYP24A1 genes are related with vitamin D deficiency in obese females. These polymorphisms may become auseful marker to predict the impending development of vitamin D deficiency in obese females. Studies have revealed that associations between genotypes of these SNPs and particular phenotypes may vary according to the following: ethnicity, interactions with environmental factors, sex, and number of participants.